Fictional Landscapes And Social Relations In Nineteenth-Century Broadside Ballads - Moreira, James (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2008)
The broadside ballad constitutes one of the oldest forms of popular culture in Europe and America. Even though our understanding of the genre, especially in North America, has been shaped by texts drawn from oral tradition, many of its thematic and stylistic traits reveal its origins in the modern popular press. The article examines the fictional landscapes of “whiteletter” ballads as represented in G. Malcom Laws catalog, especially categories “M” through “P.” These ballads all have love relationships as their central theme, and yet the spaces occupied by the principal characters and the manner in which the relationships unfold show a marked concern for larger social issues, such as separation through emigration, interclass tensions, and the influence of bureaucratic institutions.